1981
DOI: 10.1172/jci110099
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of human leukocyte elastase by platelet factor 4. Physiologic, morphologic, and biochemical effects on hamster lungs in vitro.

Abstract: A B S T R A C T The purpose of this study was to determine if human platelet factor 4 (PF4) stimulates human leukocyte elastase (HLE) against lung elastin. Lung elastin was purified from hamster lungs and tritiated by reduction with NaB3H4. We found that HLE activity against this substrate is increased by concentrations of PF4 as low as 1.6 ,ugml, and that this stimulation increased linearly with additional PF4. Lungs removed from hamnsters and inflated with solutions containing buffer alone, low dose HLE, HLE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1982
1982
1992
1992

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…That other platelet constituents also may interact with granulocytes and render them more cytotoxic has not been excluded and may be important. For instance, platelets amplify granulocyte adherence to nylon fibers (23), and others have shown platelet Factor IV can increase the activity of granulocyte proteases such as elastase (24). Moreover, evidence has been provided that thrombin-stimulated but not resting platelets (in the presence of endotoxin) enhance granulocyte adherence to nylon fibers (25), further implicating constituents ofthe platelet-release reaction in granulocyte function.…”
Section: Discussionmentioning
confidence: 99%
“…That other platelet constituents also may interact with granulocytes and render them more cytotoxic has not been excluded and may be important. For instance, platelets amplify granulocyte adherence to nylon fibers (23), and others have shown platelet Factor IV can increase the activity of granulocyte proteases such as elastase (24). Moreover, evidence has been provided that thrombin-stimulated but not resting platelets (in the presence of endotoxin) enhance granulocyte adherence to nylon fibers (25), further implicating constituents ofthe platelet-release reaction in granulocyte function.…”
Section: Discussionmentioning
confidence: 99%
“…The cationic agents, which include platelet factor 4 (PF4) and histones, probably act by occupying anionic, nonproductive sites and thus directing HLE activity to productive binding sites such as alanine or valine residues (34). Indeed, studies have shown that PF4 can potentiate HLE-induced emphysema (35). While additional studies are needed, it is unlikely that PF4 would have a similar influence on PR-3 because of its substantially lower pl.…”
Section: Discussionmentioning
confidence: 99%
“…Some previously defined functions of PF4, including modulation of the activity of collagenase and elastase (13,14) and stimulation of PMN leukocyte and monocyte chemotaxis (15), appear to result from one or more complex molecular and cellular events. Other functions of PF4, such as the binding and neutralization of heparin (16), are determined largely by charge interactions.…”
Section: Discussionmentioning
confidence: 99%